74.1k views
2 votes
Factor completely. x^3 + 2x^2 - 15x

A. -3x(x+5)(x+1)
B. x(x+5)(x+3)
C. x(x-3)(x+5)
D. 5x(x+1)(x-3)

User Tamera
by
5.3k points

2 Answers

3 votes

Answer:

C. x(x - 3)(x + 5)

Explanation:


x^3+2x^2-15x=x(x^2+2x-15)=x(x^2+5x-3x-15)\\\\=x(x(x+5)-3(x+5))=x(x+5)(x-3)

User Somewhatoff
by
5.3k points
6 votes

Answer:

c x( x+5) (x-3)

Explanation:

x^3 + 2x^2 - 15x

First factor out the greatest common factor x

x( x^2 + 2x - 15)

What 2 numbers multiply together to give us -15 and add together to give us 2

5*-3 = -15

5+-3 = 2

x( x+5) (x-3)

User Tochi
by
5.0k points